The Effect of Autocratic, Participative, and Delegation Leadership on Work Motivation of Indonesian Navy Personnel - Warsono, Heribertus Yudho; Budiyanto; Riduwan, Akhmad (International Journal of Scientific Research and Management (IJSRM), 2019)
The purpose of the study was to determine the effect of autocratic leadership style (X1), participatory (X2) and delegation (X3) on work motivation (Y) Navy Personnel. The research method used was a questionnaire with a sample of 55 people. Measurement of variables using Linkert scale techniques with 1-5 weighting values. To find out the relationship between variables X1, X2 and X3 to Y using statistical techniques correlation analysis, simple linear regression, and multiple linear regression, and to test the significance level using the test which is processed using the Statistical Product and Service Solution (SPSS) version 15 program. The conclusion of this study is that there is a strong influence from the autocratic leadership style, participatory and delegation on the work motivation of the Indonesian Navy Personnel. Then it was recommended to the Leaders at the Indonesian Navy Officers, to be able to maintain and continue to develop autocratic leadership styles, participatory leadership styles, and Delegation leadership styles to better achieve organizational goals. Increased work motivation can be done by increasing the ability of officers through training or leadership for Navy Personnel who have good work performance, giving incentives or rewards to outstanding soldiers and civil servants.